A compreensão de licenciandos em Química sobre o processo de ensino e aprendizagem - Maria Luiza Silva Tupy Botelho (2017)
This research had the purpose of analyzing the understanding of Chemistry teachers trainee who participated/are participating in teaching initiation programs (PIBID and Projetos Práticas Motivadoras de Química) on the role of teacher, student and knowledge in the teaching and learning process. We used as a data collection instrument a quiz and a focus group. The quiz was proposed with basic questions aiming at identifying the understanding of Chemistry teachers trainee about the role of the teacher, student and knowledge in the teaching and learning process, as well as the imaginary of each one about the professional performance, as educators. After analyzing the quiz, we organized the focus group with those teacherss trainee who presented well-established conceptions (more traditional or based on the current discussions of the teachings area) about what we were investigating. This stage had the expectation of reducing the degree of inference of the researchers, adding information about the opinion of the Chemistry teachers trainee on the points raised in the quiz and better understanding the points that eventually became incomplete. For the analysis of the quiz and the focus group, the Content Analysis methodology proposed by Bardin (1977) was used. Through the analysis of content, we noticed that the Chemistry teachers trainee, involved in the research, mostly present a conception of the role of the teacher and the student consistent with the discussions carried out in these Projects and in the current literature of the teachings area. The conception of these Chemistry teachers trainee on the role of scientific knowledge is less consolidated. It seemed to us that most of the future teachers involved in the research value the scientific content to the detriment of the citizen training. The teachers trainee researched are aware of the importance of inserting contemporary trends in teaching and learning in their classes, they argue that they will use these strategies when they act as teachers, but present a notion of planning with more focus on the concepts that intend to work than on the educational objectives . The teaching initiation programs are important for the training of the subjects involved in the research, as they place them in an experience with "other" ways of giving classes, in addition to the one in which they were formed. Understanding the role of teacher, student, and knowledge is consistent with the current discussion of the area, although it still needs to evolve in some cases. They were able to understand the need to motivate and engage students in class by using contemporary trends in teaching and learning. We emphasize that, when they are inserted in the field for which they are being trained during the entire course, the teachers trainee tend to relate the theoretical knowledge with the teaching practice, more than they would be able if these projects had not happened.